Dichlorodiphenyltrichloroethane Impairs Amyloid Beta Clearance by Decreasing Liver X Receptor α Expression - Wu, Dongmei; Hu, Yang; Song, Min; Li, Gongbo (Frontiers in Aging Neuroscience, 2021)
Abnormal amyloid beta (Aβ) clearance is a distinctive pathological mechanism for Alzheimer’s disease (AD). ATP-binding cassette transporter A1, which mediates the lipidation of apolipoprotein E, plays a critical role in Aβ clearance. As an environmental factor for AD, dichlorodiphenyltrichloroethane (DDT) can decrease ATP-binding cassette transporter A1 (ABCA1) expression and disrupt Aβ clearance. Liver X receptor α (LXRα) is an autoregulatory transcript factor for ABCA1 and a target of some environmental pollutants, such as organophosphate pesticides. In this study, we aimed to investigate whether DDT could affect Aβ clearance by targeting LXRα. The DDT-pretreated H4 human neuroglioma cells and immortalized astrocytes were incubated with exogenous Aβ to evaluate Aβ consumption. Meanwhile, cytotoxicity and LXRα expression were determined in the DDT-treated cells. Subsequently, the antagonism of DDT on LXRα agonist T0901317 was determined in vitro. The interaction between DDT and LXRα was predicted by molecular docking and molecular dynamics simulation technology. We observed that DDT could inhibit Aβ clearance and decrease the levels of LXRα mRNA and LXRα protein. Moreover, DDT is supposed to strongly bind to LXRα and exert antagonistic effects on LXRα. In conclusion, this study firstly presented that DDT could inhibit LXRα expression, which would contribute to Aβ clearance decline in vitro. It provides an experimental basis to search for potential therapeutic target of AD.